The role of parenting in forming independent character and discipline - Lutfi Mahera Saputri; Saiful Anwar; Happy Susanto; Sigit Dwi Laksana (Journal of diversity in learning (JDIL), 2022)
Our nation seems to have lost the local wisdom that has become the nation's cultural character since centuries ago. Some of the many cases that occur in Indonesia are the influence of association and morals and beliefs, which significantly affect the nature of students. The process of nurturing the independence and discipline of students is very influential in shaping the character of students who will become more mature and obedient to existing regulations. This study aims to determine how the role of caregivers in shaping the independent character and discipline of students at Al Mawaddah Islamic Boarding School Coper Ponorogo. This research uses a qualitative approach. The formation of independent and disciplined character in the research location has been carried out starting from the beginning of the acceptance of new students. The rules that must be obeyed have been listed from the start. The consequences that are accepted if you violate the laws must also be understood by the students. Supporting factors in forming independent and disciplined characters, the presence of colleagues who can increase the students' enthusiasm in carrying out the activities carried out. While the inhibiting factors include students who do not feel at home in a boarding house, it is challenging to build their character because they are still adapting to a new atmosphere with a new life.